99.3k views
0 votes
15(y - 4) - 2 (y - 2 )= - 5 (y+ 6)

pls solve fast
step by step

User BigL
by
7.2k points

2 Answers

1 vote

Answer:

13/9

Explanation:

Step 1: simplify

15y-60-2y+4= - 5y-30

Step 2: group like terms together

18y= 26

Step 3: simplify

y=13/9

User Danie
by
6.8k points
6 votes

Answer:

y= 13/9

Explanation:

we apply distributive property:

15(y - 4) - 2 (y - 2 )= - 5 (y+ 6)

15*y-15*4 -2*y +2*2 = -5*y -5*6

we have:

15y - 60 -2y +4 = -5y -30

13y - 56 = -5y -30

13y+5y =56 - 30

y= 26/18

so y = 13/9

User Adamfinstorp
by
6.9k points